2023
DOI: 10.1088/2752-5295/accb03
|View full text |Cite
|
Sign up to set email alerts
|

US farmers’ adaptations to climate change: a systematic review of adaptation-focused studies in the US agriculture context

Abstract: Farmers in the US are adopting a range of strategies to deal with climate change impacts, from changing planting dates to using sophisticated technologies. Studies on farmers’ adaptation in US agriculture focus on a variety of topics and provide an understanding of how farmers adapt to climate change impacts, which adaptation strategies offer better outcomes, and what challenges need to be addressed for effective adaptations. Nevertheless, we lack a comprehensive view of adaptation studies focusing on US farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…This list is not exhaustive and NbS such as cover crops and diversified crop rotations are already widely used practices in sustainable farming. US farmers are undertaking five broad categories of climate adaptation strategies based on NbS: water management, crop management, nutrient management, technological management, and financial management [62]. Our study has shown that many small-scale farmers, ranchers, and other LFE-types are familiar with and practicing NbS.…”
Section: Current Uptake Of Nbsmentioning
confidence: 92%
See 1 more Smart Citation
“…This list is not exhaustive and NbS such as cover crops and diversified crop rotations are already widely used practices in sustainable farming. US farmers are undertaking five broad categories of climate adaptation strategies based on NbS: water management, crop management, nutrient management, technological management, and financial management [62]. Our study has shown that many small-scale farmers, ranchers, and other LFE-types are familiar with and practicing NbS.…”
Section: Current Uptake Of Nbsmentioning
confidence: 92%
“…[5,11,13,22,62,63] Pathway 2: Peer-to-peer (P2P) and Expert-to-peer (E2P) knowledge co-creation and exchange LFEs possess a keen awareness of weather patterns and climatic conditions that affect them on a daily basis. They continuously adapt to changes in both short-term and long-term weather and climate variability.…”
mentioning
confidence: 99%
“…The literature review shows that a comprehensive discussion has unfolded in the scientific community on the global impact of climate change and adaptation to it on various aspects of human life [19,27,28,37,38,43,[49][50][51][52][53][54][55][56]. The multiple attempts are devoted to research involving systematic analysis, categorization and documentation of agricultural adaptation as a whole [23,25,32,39,45,[57][58][59], as well some specific aspects, such as adaptation features in different countries and regions of the world, e.g.,: the Mediterranean region [60], Eastern Europe [61], Nordic countries [33], the USA [62], Canada [39], developing countries [63], low-and middle-income countries [42], Asia [64][65][66], South Asia [67], African countries [11,18,68], arid and semi-arid tropics of Asia, Africa, and Latin America [69]; in various sectors of agriculture [70], depending on the effects for various crops [71][72][73][74][75]…”
Section: Adaptation Strategies For Agricultural Development and Produ...mentioning
confidence: 99%